Liver resection for hepatocellular and fibrolamellar carcinoma in a South African tertiary referral centre - Ziaei, Yalda (Division of General Surgery, 2025)
Hepatocellular carcinoma (HCC) is the most common primary liver malignancy in adults and is the fifth most common solid tumour worldwide with a variable prevalence based on underlying risk factors and geography. The incidence has risen over the past several decades and HCC is now the third leading cause of cancer-related deaths globally, after lung and stomach cancers, with a 5-year survival rate less than 20% and recurrence rates as high as 88%. More than 80% of global HCCs occur in sub-Saharan Africa (SSA) and Eastern Asia where the incidence ranges from 4.8 to 8.3 per 100,000 per year in different regions of SSA with the highest incidence in the western central Africa compared to less than 3 per 100 000 in Western countries. Hepatocellular carcinoma has become a significant public health concern in SSA and is now the second leading cancer in men and the third for women, occurring in particular in young adults. Unfortunately only a small proportion of patients in SSA with HCC are treated with curative intent. Data are scarce, but studies consistently report that curative-intended treatment is pursued in less than 1% of patients in SSA with HCC. Fibrolamellar carcinoma (FLC) was until recently regarded as a variant of HCC occurring in young patients with a relatively good prognosis but is now recognized as a distinct clinical entity with consistent chimeric fusion protein (DNAJB1-PRKACA) expression by FLC tumours. The optimal treatment of HCC and FLC is influenced by the stage of the disease, the degree of liver impairment, and patient performance status. Currently, the therapeutic strategy is based on international guidelines and the Barcelona Clinic Liver Cancer (BCLC) staging system in which potentially curative treatment for early-stage HCC includes resection, transplantation and ablation. Surgical resection is the treatment of choice in patients without cirrhosis and in those with cirrhosis and well-preserved hepatic function. Despite advances in surgical techniques and perioperative care, hepatectomy remains a high-risk surgical procedure with complications occurring in up to 40% of resections. This adds a significant burden to individual patients by adversely affecting quality of life and increasing length of hospital stay, readmission rates, and healthcare costs. Recurrence despite curative-intent treatment is as high as 88% and is due to tumour multifocality, size ≥5 cm, macroscopic vascular or microscopic lymphovascular invasion, elevated alfa-fetoprotein (AFP) levels and impaired liver function. Previous publications from our unit have reported earlier data on resection for HCC and FLC. The aim of this research was to assess the peri-operative outcome and survival of patients with HCC and FLC following curative liver resection at a tertiary referral centre in South Africa. In this study a retrospective analysis was done of all liver resections for HCC and FLC at Groote Schuur Hospital and the University of Cape Town Private Academic Hospital between January 1990 and December 2021. Three resection groups were compared, (i) HCC occurring in normal livers, (ii) HCC occurring in cirrhotic livers, and (iii) fibrolamellar carcinoma. Post-operative complications were classified according to the expanded Accordion severity grading system. Median overall survival (OS) and 95% confidence intervals (CI) were calculated. Forty-eight patients were included in the study, 25 with HCC in non-cirrhotic livers, 15 in cirrhotic livers and eight for FLC. Thirty-six patients (75%) underwent a major resection. No mortality occurred but 16 patients (33%) developed grade 1 to 4 complications. Thirty-three patients (68%) developed recurrence of HCC following their initial resection of whom 29 (60%) ultimately died. Median OS was 64.2m, 95% CI [29.7-84.6], 61.9m, [28.1-95.6] and 31.7months, [1.5-61.8] for patients with HCC in non-cirrhotic livers, FLC and HCC in cirrhotic livers respectively. Liver resection for HCC and FLC was a safe procedure with no mortality, but one-third of patients had associated post-operative morbidity. The high long-term recurrence rate remains a major obstacle in achieving better survival results after resection.